METHOD FOR AUTOMATIC RAISING AND LEVELING OF SUPPORT PLATFORM - A. G. Stryzhniou (Informatika)
The paper presents the method for automatic raising and leveling of support platform that differ from others in simplicity and versatility. The method includes four phases of raising and leveling when performance capabilities of the system is defined and the soil condition is tested. In addition, the current condition of the system is controlled and corrected with the issuance of control parameters to the control panel. The method can be used not only for static, but also for dynamic leveling systems, such as active suspension. The method assumes identification and dynamics testing of reference units. The synchronization of reference units moving was implemented to avoid dangerous skewing of support platform. The recommendations for the system implementation and experimental model identification of support platform are presented.